Darwin impact glass study by Raman spectroscopy in combination with other spectroscopic techniques. (24th May 2015) - Gomez‐Nubla, L.; Aramendia, J.; Alonso‐Olazabal, A.; Fdez‐Ortiz de Vallejuelo, S.; Castro, K.; Ortega, L. A.; Zuluaga, M. C.; Murelaga, X.; Madariaga, J. M.; Marshall, Craig P.
<x xml:space="preserve">Abstract</x> Darwin impact glass appeared in Tasmania (Australia) around 800 000 years ago by meteorite impact. To further study the formation process, several specimens of Darwin glass from the meteorites collection of the University of the Basque Country were analysed. Raman spectroscopy was considered the most suitable technique to determine the differences in composition between the surface layer and the inner matrix. These analyses were complemented by other techniques such as Scanning Electron Microscopy Energy Dispersive X‐Ray Spectroscopy, Electron Micro Probe Analysis and Energy Dispersive X‐Ray Fluorescence. The major elements found were Si, Al, Fe, K and Ca, together with a range of minor elements Ti, Cl, Zr, Ba, S, Cr, Mn, Ni and Sr. On the micrometre scale, highly heterogeneous elemental composition was found in the glassy matrixes, in particular a gradient in the concentration of iron and aluminium. Raman spectroscopy identified the characteristic silica vitreous matrix of impacted glasses with small inclusions of α‐cristobalite (a mineral phase that indicates high temperature formation) and vesicles with iron or iron and nickel oxides filling the pores. Finally, malachite [Cu2CO3(OH)2], ponsjankite [Cu4SO4(OH)6 · H2O] and covellite (CuS) were identified by Raman spectroscopy formed after impact as secondary minerals due to the weathering of copper ore deposits incorporated to the matrix. Copyright © 2015 John Wiley & Sons, Ltd.